ChemInform Abstract: Highly Stereoselective Generation of Complex Oxy‐Bicyclic Scaffolds via an Atom‐Economic Pd(II)‐Catalyzed Hydroalkynylation, Isomerization and Diels—Alder Cycloaddition Sequence. Issue 32 (12th August 2014) - Shen, Ruwei; Chen, Ke; Deng, Qiulin; Yang, Jianjun; Zhang, Lixiong
Abstract: The new cascade reaction proceeds with high regio‐ and stereoselectivity, and tolerates a wide range of functionality and structural motifs.